Il trattamento delle condropatie degenerative con tessuto adiposo autologo microframmentato - Russo, A.; De Caro, F.; Condello, V.; Collarile, M.; Madonna, V. (Lo Scalpello - Journal, 2019)
TREATMENT OF DEGENERATIVE CARTILAGE LESIONS WITH MICRO-FRAGMENTED AUTOLOGOUS ADIPOSETISSUEOsteoarthritis is a widespread pathology, with a prevalence of over 50% of the population, which leads to pain andfunctional limitation. At the moment, no surgical technique has been shown to be capable of real regeneration of thechondral layer. The new regenerative frontier seems to be represented by the self-ability of the Stromal VascularFraction (SVF) to preserve the cellular network, which is essential for cell regeneration. Several micro-fragmentedadipose tissue extraction and processing systems have been refined in the past years and recent literature data showthe biological effectiveness of this tissue, which plays a key role in restoring joint homeostasis, through the modulationof inflammation and pain. It will be necessary and important to understand whether this injective method can reallybe considered a “regenerative” option.